Manajemen Kepemimpinan Kepala Madrasah Terhadap Kinerja Guru Madrasah Aliyah Jeumala Amal Lueng Putu – Pidie Jaya Tahun Pelajaran 2024/2025 - Zuljalali Wal Ikram (UNISAN JURNAL, 2025)
This study aims to analyze the influence of madrasa head leadership management on teacher performance at Madrasah Aliyah Jeumala Amal Lueng Putu, Pidie Jaya, for the 2024/2025 academic year. In the context of education in Indonesia, the role of the head of the madrasa is central in creating an environment conducive to the professional development of teachers and students. The method used in this research is quantitative with a survey approach. Data was collected through questionnaires distributed to teachers at the madrasa and analyzed using regression analysis techniques. The results of the study indicate a positive and significant influence between madrasa head leadership management and teacher performance. These findings show that good leadership can enhance teacher motivation and professional performance, which in turn positively impacts the quality of education. Therefore, madrasa heads need to implement effective leadership strategies to improve teacher performance within the madrasa environment.